Streptococcus bovis – unusual etiology of meningitis in a neonate with Down syndrome: a case report - Mettananda, Sachith (J Med Case Rep, 2018)
BACKGROUND: Common etiological agents of neonatal meningitis include group B Streptococcus, Escherichia coli, and Staphylococcus aureus. Here we report a rare pathogen – Streptococcus bovis – causing meningitis in a premature neonate with Down syndrome. CASE PRESENTATION: A 26-day-old Asian male neonate with Down syndrome presented with a history of high-grade fever, poor sucking, poor cry, and reduced activity. On admission, he was febrile and had features of circulatory collapse. A cerebrospinal fluid examination confirmed bacterial meningitis and blood culture isolated the causative organism: group D Streptococcus, which was verified as Streptococcus bovis biotype 2. An echocardiogram did not show evidence of infective endocarditis. CONCLUSIONS: This is probably the first report of neonatal meningitis due to Streptococcus bovis in a child with Down syndrome. Although our patient did not show features of overt immunodeficiency, subtle abnormalities in his immune system would have predisposed him to infection with this unusual organism. This case highlights the need for considering unusual pathogens when managing serious infections in children with Down syndrome.